Service excellence in UK retail banking: customers' perspectives of the important antecedents. Issue 7 (5th October 2015) - Sekhon, Harjit Singh; Al-Eisawi, Dima; Roy, Sanjit Kumar; Pritchard, Adrian
Abstract : Purpose: – The purpose of this paper is to develop and tests a service excellence model, thus providing a detailed understanding of the key antecedents of service excellence, from a customer ' s perspective. The model presented in this paper is rooted in cross-disciplinary literature and tested amongst customers of UK retail banking services. Design/methodology/approach: – Following a systematic approach to scale development, the paper draws on survey data from 260 consumers of retail banking products, with the data collected on national basis in the UK. Findings: – The theoretical framework was evaluated using a structural approach. Of the hypothesised antecedents, innovation has the greatest impact on service excellence while reputation the least, as far as customers are concerned. Research limitations/implications: – The research was limited to one research domain, i.e. UK retail banking, and thus it is reasonable to hypothesise that other aspects of service excellence will be more or less relevant for other types of financial services or in other geographic regions. Practical implications: – Given the challenges faced by the retail banking sector, there are implications for practitioners because the authors identified the key antecedents of service excellence. The antecedents can be used by practitioners to help demonstrate excellence on their part and they could differentiate what are homogenous services at a time when the retail banks are going through a period of recovery following the crisis within the sector. Originality/value: – This work complements the understanding of service excellence and provides insight for scholars and practitioners by modelling services for a specific service sector.